Canadian Volunteers: Spain 1936-1939 - Horn, Michiel (Labour / Le Travail, 1991)
The article reviews the book, "Canadian Volunteers: Spain 1936-1939," by William C. Beeching.
Keywords: BEECHING, William C.; BOOKS -- Reviews; CANADIAN Volunteers: Spain 1936-1939 (Book); Nonfiction; Volunteers